First record of the Blue Striped Hermit Crab, Clibanarius longitarsus (decapoda, crustacea) from Sunderbans mangrove forest, Bangladesh - Hossain, Mostafa Ali Reza; Naser, M Niamul; Khan, M Golam Quader; Fatema, Mst Kaniz; Rouf, Muhammad Abdur; Sultana, Selina; Noman, Muhammed (Bangladesh Journal of Zoology, 2015)
Blue Stripped hermit crab, Clibanarius longitarsus (De Haan, 1849) was collected from Kalagachhia, Satkhira Forest Range of Sundarban Mangrove Forest on 18 April 2015 during an exploration of the IUCN Crustacean Exploration Team. This crustacen decapod was recorded for the first time from Bangladesh geographical area. Bangladesh J. Zool. 43(1): 131-135, 2015